(untitled) (SMC Journal of Sociology, 2025)
Violence, as defined by the WHO, is a pervasive issue globally, with the intentional use of force leading to harm, injuries, or death. In Nepal, gender-based violence is significant, affecting domestic settings and leading to societal acceptance of violence against women. A systemic issue, violence is often underreported due to cultural norms and societal expectations. The prevalence of domestic violence underscores the need for a comprehensive framework to combat this issue, emphasizing the role of patriarchy in perpetuating violence against women. Statistics indicate high levels of violence against women, stemming from deep-rooted patriarchal beliefs that reinforce male dominance and women’s subordination. The research focuses on exploring domestic violence in the Madhesh region, delving into the physical manifestations of violence against women. A critical analysis of theoretical frameworks, particularly patriarchy, reveals how societal norms shape unequal gender relations and perpetuate violence, hindering women’s autonomy. By addressing patriarchal structures and promoting gender equality, efforts can be made to combat domestic violence and create a safer environment for all individuals.